A Sighting of an Albino Caribou in Alaska and Review of North American Records - Curatolo, James A. (ARCTIC, 1979)
An albino caribou (Rangifer tarandus granti) calf was observed among members of the Porcupine Herd on 2 July 1976 near the Kongakut River in northeastern Alaska (69° 27' N, 141° 30' W). It had snow-white fur and pink eyes. Hooves and muzzle were light-colored. The calf's behavior was similar to normally pigmented calves. This individual was the only albino observed in a group of 15,000 to 20,000 individuals. Observations were made for approximately two minutes at 300 m using a 45 power spotting scope. Eight other people observed the calf. .